La desintegración familiar y su influencia en el rendimiento académico de los estudiantes de decimo año de educación básica del Colegio Nacional Técnico Arenillas sección diurna de la ciudad de Arenillas, periodo 2012-2013. - Castillo Benavidez, Herica Jesús (2013)
The family is the primary and most powerful emotional system they belong to human beings and is the largest potential resource, the emotional ties between members play different roles the individual, connecting with each other throughout their lives and even after his death , transcending time, distance and conflicts, thus contributing to the society in which it is immersed.